2008
DOI: 10.1097/nen.0b013e31815f3899
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Changes in the Thalamocortical System of Cathepsin D-Deficient Mice

Abstract: Cathepsin D (CTSD; EC 3.4.23.5) is a lysosomal aspartic protease, the deficiency of which causes early-onset and particularly aggressive forms of neuronal ceroid-lipofuscinosis in infants, sheep, and mice. Cathepsin D deficiencies are characterized by severe neurodegeneration, but the molecular mechanisms behind the neuronal death remain poorly understood. In this study, we have systematically mapped the distribution of neuropathologic changes in CTSD-deficient mouse brains by stereologic, immunologic, and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 33 publications
6
75
1
Order By: Relevance
“…PGRN is therefore likely to be primarily implicated in lysosomal biogenesis that leads to microglial activation and microgliosis. In the present study, we showed that aged PGRNdeficient mice presented with increased accumulation of p62 and ubiquitin in the VPM/VPL, where the main pathological changes have been observed in reported NCL model mice [15][16][17][18]. p62/ubiquitin inclusions have been observed when the autophagy-lysosomal system is disrupted [26].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…PGRN is therefore likely to be primarily implicated in lysosomal biogenesis that leads to microglial activation and microgliosis. In the present study, we showed that aged PGRNdeficient mice presented with increased accumulation of p62 and ubiquitin in the VPM/VPL, where the main pathological changes have been observed in reported NCL model mice [15][16][17][18]. p62/ubiquitin inclusions have been observed when the autophagy-lysosomal system is disrupted [26].…”
Section: Discussionmentioning
confidence: 64%
“…These pathological changes in aged PGRN-deficient mice are partially consistent with previous studies [11,13,33], though the brain regions examined were different. Analyses using NCL model mice in the previous studies revealed that glial activation precedes neuronal loss in the VPM/VPL [17,34]. Therefore, the particular vulnerability of the VPM/VPL in PGRN-deficient mice might be attributed to cytotoxicity of glial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, we have been characterizing each of the available mouse models of NCL, documenting the onset and progression of pathological changes [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and testing the efficacy of a range of therapeutic interventions [35][36][37][38]. Our studies have revealed a number of new and surprising pathological features that are broadly shared by the different forms of NCL, but with subtype-specific differences in the staging of these events and some more pronounced differences between certain forms of NCL.…”
Section: What Do We Know About Ncl Pathogenesis So Far?mentioning
confidence: 91%
“…Synaptic alterations have previously been suggested as initiating events causing NCL in the CLN5-knockout sheep 22 and in a mouse model of lysosomal disease due to a defect in cathepsin D function (CLN10). 23 Overall, the data suggest that macular photoreceptors appear to be most sensitive to mutations in MFSD8. Extramacular photoreceptors are the next most vulnerable, with cortical neurons being the most resistant of the affected cell types.…”
Section: Figurementioning
confidence: 91%